Chemistry: A Place to Publish Your Creative Multidisciplinary Research - Alabugin, Igor V. (Chemistry an international journal, 2023)
It is my pleasure to welcome you to Chemistry (ISSN: 2624-8549), an open access peer-reviewed journal that publishes both primary reports and reviews highlighting important advances in fundamental areas of chemistry and/or illustrating the central role of chemistry in bridging the physical and life sciences [...]